influence of vegetation type, soil properties and precipitation on the composition of soil mite and microbial communities at the landscape scale - Nielsen, Uffe N.; Osler, Graham H. R.; Campbell, Colin D.; Burslem, David F. R. P.; van der Wal, René (Journal of biogeography, 2010)
We used a landscape-scale study of birch invasion onto heather moorland to determine the consistency of changes in vegetation type and soil properties and in the community composition of five soil organism groups. Our aim was to determine whether the degree to which soil organisms respond to natural changes and/or induced changes (e.g. changes in land-use type and climate) in habitat is consistent across trophic and taxonomic groups in the context of conservation policies for birch woodland and heather moorland. Mainland Scotland. We sampled mesostigmatid mites, oribatid mites, fungi, bacteria and archaea in adjacent patches of birch woodland (dominated by Betula pubescens) and heather moorland (dominated by Calluna vulgaris) at 12 sites for which annual rainfall ranged between 713 and 2251 mm. Differences in community composition were visualized using non-metric multidimensional scaling based on Bray-Curtis dissimilarities. The factors contributing to differences between habitats within sites were explored using general linear models and those among sites using redundancy analysis. The communities of all groups differed between habitats within sites, but only the oribatid mites and fungi differed consistently between habitats across sites. Within sites, dissimilarity in fungal communities was positively related to the difference in C. vulgaris cover between habitats, whereas dissimilarities in bacteria and archaea were positively related to differences in soil pH and C:N ratio between habitats, respectively. The influence of vegetation type and soil properties differed between groups of soil organisms, albeit in a predictable manner, across the 12 sites. Organisms directly associated with plants (fungi), and organisms with microhabitat and resource preferences (Oribatida) were strongly responsive to changes in habitat type. The response of organisms not directly associated with plants (bacteria, archaea) depended on differences in soil properties, while organisms with less clear microhabitat and resource preferences (Mesostigmata) were not strongly responsive to either vegetation type or soil properties. These results show that it is possible to predict the impact of habitat change on specific soil organisms depending on their ecology. Moreover, the community composition of all groups was related to variation in precipitation within the study area, which shows that external factors, such as those caused by climate change, can have a direct effect on belowground communities.